The Application of Community-Based Economic Model in Entrepreneurial Activities - Sukristin Sukristin; Mastiah Mastiah (Muhammadiyah University Press, 2014)
One of the efforts to increase people's income is by applying economic models that are suitable for the community. This model places emphasis on lower class community economic empowerment so that eventually they can be economically self-sufficient. To apply an economy model suitable for that particular source, around the area of Sungai Melayu, particularly Piansak village is one of the efforts suggested. The method applied for this research is Action Research. For the first year, the main task is to identify the local area. Only after a feasibility study being done on the data found, then a system of Society Economy Model will be implemented accordingly. The further steps will follow based on the result yielded of first-year-research. The potential businesses suitable to the area, possibly will be businesses in raising livestock or poultry, such as